"Was Definitely Different Because They Were Kids": Caring for Patients From a School Shooting. Issue 5 (September 2022) - McCall, W. Travis; Anderson, Joel G.; Myers, Carole R.; Sagherian, Knar; Bamwine, Patricia
Abstract : BACKGROUND: Trauma nurses may experience secondary traumatic stress, compassion fatigue, and burnout as their clinical roles expose them to patients with traumatic injuries. Because traumatic events described as being most stressful for nurses involve sudden death or children and adolescents, multicasualty, school-associated shooting events are likely to be particularly stressful for nurses who care for the affected patients. OBJECTIVE: This research examined the psychosocial effects of caring for patients in an inpatient trauma unit following a multicasualty, school-associated shooting event. METHODS: This research was guided by a qualitative case series approach, a theory of secondary traumatic stress, and the compassion fatigue resilience model. Registered nurses who provided care in the trauma unit of a Level I trauma center to patients who were injured during a multicasualty, school-associated shooting event in the Southeastern United States were invited to participate. RESULTS: The three themes identified by this research were (a) innocence of the patients, (b) trajectories of increased emotions, and (c) processing emotional stressors. Nurses reported the benefits of peer support and provided recommendations to increase the efficacy of formal debriefing sessions. CONCLUSIONS: Nurses value self-care routines and peer support as coping mechanisms to foster well-being following exposure to traumatic events. Hospitals should encourage active participation in timely critical incident stress debriefings and promote the use of employee assistance services to support nursing staff after these events.